Computer dictionary with helpful terms in mathematics - Mendoza, Grette A.; Joseph, Alexander E.; Madrigal, Caye B. (SmartBooks Pub., 2004)
Terms that are used and included in this dictionary are the most common (as of publication) and easy to understand in the fields of computer hardware/software and mathematics. Some terms contain examples that will serves as a guide for the users, especially for beginners.